Co-morbidities among epilepsy patients: experience in Bangladesh (Bangladesh Journal of Medicine, 2014)
Objective: To determine comprehensively all the major comorbid diseases observed among epilepsy patients. Methods: In this observational study, 1168 patients were recruited from outpatient based epilepsy clinic in a tertiary care hospital. Four categories of comorbid conditions namely neuropsychiatric, developmental (mental retardation, cerebral palsy), pain disorder (migraine) and others (hypertension, diabetes, stroke) were evaluated in these patients through a prefilled questionnaire and data were then analyzed. Epilepsy were broadly classified into generalized epilepsy (GE), localization related epilepsy (LRE), symptomatic and unclassified. Result: Among the 1168 subjects we included in this study, 71.5% were male. The most common age group at the time of interview was 11-20 years (36.8%). Only 29 (2.5%) respondents were older than 60 years. Among the listed comorbid conditions, mental retardation was the most common entity (15.5%), followed by psychiatric disorder (12.8%), hypertension (5.6%), migraine (5.4%) and cerebral palsy (5.0%). Only 1.5% had diabetes and 0.6% had stroke. Mental retardation and cerebral palsy were more common and significantly associated (p=0.0001 and 0.005) with GE patients (95 and 44), psychiatric disorder was also common among GE patients (108)) with a p value of 0.0001. But migraine was more common and significantly associated (p=0.0001) with LRE patients (46). Stroke was only present in symptomatic epilepsy group (7) and diabetes was present only in GE patients (19). Both were significant (p= 0.0001 and 0.01). But hypertension among different epilepsy groups was not significant (p=0.08). Conclusion: Neuropsychiatric, developmental and pain disorder are common comorbid associations within different epilepsy syndromes which may need special care during management of epilepsy patients. DOI: http://dx.doi.org/10.3329/bjmed.v24i2.20219 Bangladesh J Medicine 2013; 24 : 65-69